PENGARUH KEMAMPUAN KONEKSI MATEMATIS DAN DISPOSISI MATEMATIS TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Risnah K; Sitti Inaya Masrura; Aprisal Aprisal (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study was to determine the influence of mathematical connection ability and mathematical dispositions on mathematics learning ourcomes for student of class XI IPS MA Pergis Campalagian. The approach which used in this research was a quantitative approach with the type of research is ex-post facto. The research sample was 37 students who were selected using the saturated sampling technique. Data collection techniques used the following instruments: (1) mathematical connection ability test, (2) mathematical disposition questionnaire, and (3) mathematics learning outcomes test. Data was analysis used descriptive analysis and inferential analysis. The result showed that: (1) the avarage mathematical connection ability is in the low category, (2) the avarage mathematical disposition is in the medium category, and (3) the avarage mathematics learning outcomes are in the low category. There are 3 hypotheses in this study with test result using simple linear regression analysis and multiple linear regression, namely: (1) mathematical connection ability had a positive and significant effect on mathematics learning outcomes, (2) mathematical disposition had a positive and significant effect on mathematics learning outcomes, and (3) mathematical connection abilities and mathematical dispositions positive and significant effect on mathematics learning outcomes